Commemorative Issue in Honor of Professor Emeritus Calvin H. Bartholomew in Anticipation of His 75th Birthday - Morris D. Argyle (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book recognizes the career of Professor Emeritus Calvin H. Bartholomew, who celebrated his 75th birthday in 2018, and his contributions to the science and engineering of heterogeneous catalysis, a field which improves daily life in countless, but often unrecognized ways. Dr. Bartholomew is an eminent researcher, an outstanding educator, mentor, and friend. The nine chapters comprising the book were written by former students, collaborators, colleagues, and respected peers. Chapters cover supported iron Fischer--Tropsch catalysts, a spectroscopic study of iron-based water gas shift catalysts, nickel catalysts both for (dry) methane reforming with associated carbon deactivation and carbon dioxide methanation, a methanol steam reforming catalyst, cobalt oxide on niobia catalysts for environmental applications, palladium catalysts supported on titania for hydrogen peroxide synthesis, methane combustion catalyst stability, and chiral catalyst deactivation. In summary, this book covers much of the breadth and points to the depth of Professor Bartholomew's illustrious career. We thank him for his kind example and honor him for his lasting contributions.